2001
DOI: 10.1067/mtc.2001.116949
|View full text |Cite
|
Sign up to set email alerts
|

T2 tumors larger than five centimeters in diameter can be upgraded to T3 in non–small cell lung cancer

Abstract: A tumor size of more than 5 cm in diameter was indicative of a poor prognosis in non-small cell lung cancer, because patients with T2b tumors had a significantly different survival from that of patients with T2a tumors, and the survival curve was located between those for patients with T3 and T4 tumors. Consequently, T2b might be upgraded to at least T3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 17 publications
2
44
0
Order By: Relevance
“…consistent with previous findings reported by Carbone and colleagues [2]. The appropriateness of initial operation in patients with pleural invasion must be determined carefully in patients with the disease.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…consistent with previous findings reported by Carbone and colleagues [2]. The appropriateness of initial operation in patients with pleural invasion must be determined carefully in patients with the disease.…”
supporting
confidence: 78%
“…However, earlier studies indicated that the surgical outcome of NSCLC with large tumors more than 5 cm in diameter is poor. Carbone and associates [2] reported that 5-year survival rate of 111 NSCLC patients with T2 tumors more than 5 cm in diameter was 35.1%. In their series, the 9 significant survival difference based on this threshold remained in N0 and N2-3 status.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A great number of studies have demonstrated that the survival of patients with SCCs is better than those with adenocarcinomas. Similarly, Carbone et al [16] detected that five-year survival probability in SCCs was better than adenocarcinomas (48.8% and 40.9%, respectively). Also, in another study, five-year survival in SCC was better than adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In peripheral tumors, adenocarcinoma incidence was 37.4% and SCC incidence was 45%, and although not statistically significant, there was a dominance of SCC. [16] According to the literature, adenocarcinoma incidence is higher in females. [17] We detected that the incidence of EBL was significantly lower in females.…”
Section: Discussionmentioning
confidence: 99%